Transformable nanoparticles to bypass biological barriers in cancer treatment. Issue 21 (3rd October 2022) - Ramachandran, Mythili; Ma, Zhao; Lin, Kai; De Souza, Cristabelle; Li, Yuanpei
Abstract : Nanomedicine provides a great strategy for emerging chemotherapeutics that can navigate the many biological barriers preventing effective drug delivery to tumors. Abstract : Nanomedicine based drug delivery platforms provide an interesting avenue to explore for the future of cancer treatment. Here we discuss the barriers for drug delivery in cancer therapeutics and how nanomaterials have been designed to bypass these blockades through stimuli responsive transformation in the most recent update. Nanomaterials that address the challenges of each step provide a promising solution for new cancer therapeutics.